Investigating the influence of acid sites in continuous methane oxidation with N2O over Fe/MFI zeolites. Issue 1 (20th October 2017) - Chow, Ying Kit; Dummer, Nicholas F.; Carter, James H.; Williams, Christopher; Shaw, Greg; Willock, David J.; Taylor, Stuart H.; Yacob, Sara; Meyer, Randall J.; Bhasin, Madan M.; Hutchings, Graham J.
Abstract : Methane oxidation using N2 O was carried out with Fe–MFI zeolite catalysts at 300 °C. Abstract : Methane oxidation using N2 O was carried out with Fe–MFI zeolite catalysts at 300 °C. Methane conversion over Fe–ZSM-5, Fe–silicalite-1 and Fe–TS-1 indicates that Brønsted acidity is required to support the Fe-based alpha-oxygen active site for the important initial hydrogen abstraction step. Increasing the calcination temperature of Fe–ZSM-5 from 550 to 950 °C showed that the catalyst retained the MFI structure. However, at 950 °C the Brønsted and Lewis acid sites were altered significantly due to the migration of aluminium, which led to a significant decrease in catalytic performance. Over Fe–ZSM-5 the desired partial oxidation product, methanol was observed to undergo a reaction path similar to the methanol to olefin (MTO) process, which predominately produced ethene and subsequently produced coke. Methanol control experiments over Fe–silicalite-1, Fe–ZSM-5, Fe–TS-1 and H–ZSM-5 indicated that with the presence of Brønsted acidity the catalysts were more effective at forming ethene and subsequent aromatic species from DME, which resulted in an increased level of catalyst fouling. The implication of these observations is that the desorption of methanol is crucial to afford high mass balances and selectivity, however, Brønsted acid sites appear to slow this rate. These sites appear to effectively retain methanol and DME under reaction conditions, leading to low mass balances being observed. Our results confirm that to afford efficient and continuous methane oxidation by N2 O, the catalytic active site must be Fe coordinated to Al.